KEBIJAKAN FISKAL MASA AL-KHILAFAH AL-ISLAMIYAH - Supriatna Supriatna; Dedah Jubaedah (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2020)
Abstract: This article describes the policy of the Islamic fiscal management system managed by the state with the aim of improving the people welfare during the Khulafa ar-Rasyidin era. This study uses a normative historical method and an exploratory approach that refers to various relevant literatures and is analyzed qualitatively. This research shows that the culture of the Islamic fiscal management system during the Khulafa ar-Rasyidin era tended to continue the Prophet's culture and development which included a balanced budget policy, as evidenced by the instruments of zakat, ghanimah, kharraj, jizyah, waqf, and others, and distributed for the welfare of society. The policy of managing the Islamic fiscal system is now widely used as a reference for developing a modern fiscal system. This result of this study found that the policy of the Prophet Muhammad regarding on fiscal management was continued by Khulafa ar-Rasyidin, which was a representation of the principles of public spending in the social, political, economics, and security context, whose it was based on the principle of a balanced budget policy. And then, the utilization of zakat, jizyah, kharaj, ghanimah, and waqf instruments as the sources of the state budget at this period, illustrating the dynamics of the caliph's fiscal policy progressively during the Khulafa ar-Rasyidin era, which was succeeded in bringing the Muslims to be in the golden age. Unfortunately, after the fall of the Abbasid Dynasty and continued to the colonialization period, Islamic fiscal policy was also declined.